2020
DOI: 10.1371/journal.pone.0239934
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a novel machine learning method to the Friedewald formula and Martin-Hopkins equation for low-density lipoprotein estimation

Abstract: Background Low-density lipoprotein cholesterol (LDL-C) is a target for cardiovascular prevention. Contemporary equations for LDL-C estimation have limited accuracy in certain scenarios (high triglycerides [TG], very low LDL-C). Objectives We derived a novel method for LDL-C estimation from the standard lipid profile using a machine learning (ML) approach utilizing random forests (the Weill Cornell model). We compared its correlation to direct LDL-C with the Friedewald and Martin-Hopkins equations for LDL-C est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Of the 17 custom RDRs live as of July 2021, academic output includes but is not limited to that from Cardiac Imaging, 30 , 31 Digestive Care, 32 Mental Health, 33 , 34 Myeloproliferative Neoplasms, 35 , 36 Pulmonary and Critical Care, 37 , 38 and Stroke. 39 Largely driven by investigators with grant funding, RDR projects have generated data marts to address specific clinical research questions (eg, predictors of outcomes in hospitalized cirrhotic patients) while also yielding generalizable resources for the institution, such as an i2b2 eye exam ontology from Ophthalmology and surgical pathology report NLP from Urology.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 custom RDRs live as of July 2021, academic output includes but is not limited to that from Cardiac Imaging, 30 , 31 Digestive Care, 32 Mental Health, 33 , 34 Myeloproliferative Neoplasms, 35 , 36 Pulmonary and Critical Care, 37 , 38 and Stroke. 39 Largely driven by investigators with grant funding, RDR projects have generated data marts to address specific clinical research questions (eg, predictors of outcomes in hospitalized cirrhotic patients) while also yielding generalizable resources for the institution, such as an i2b2 eye exam ontology from Ophthalmology and surgical pathology report NLP from Urology.…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning provides an improved performance of modeling and outcome prediction in cardiovascular medicine. Several studies have developed machine learning methods to better estimate LDL-C levels ( 14 16 ). Lee et al ( 14 ) developed a DNN model for estimating LDL-C including 180 perceptrons, which was motivated by the novel method from the standard lipid profile (TC, HDL-C, and TG).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 14 ) developed a DNN model for estimating LDL-C including 180 perceptrons, which was motivated by the novel method from the standard lipid profile (TC, HDL-C, and TG). Singh et al ( 16 ) proposed a machine learning method utilizing random forests for LDL-C estimation using a direct LDL-C as a reference value. Tsigalou et al ( 15 ) suggested a machine learning model to estimate LDL-C using shallow and deep machine learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…But our study demonstrated lesser correlation coefficient (0.90) in the group of patients with triglyceride >400 mg/dL for the random forests model. 25…”
Section: Discussionmentioning
confidence: 99%
“…24 Random forests model was used in a study to predict LDL-C, and the performance was found to better than Friedewald and Martin formulas. 25…”
Section: Introductionmentioning
confidence: 99%